Wasps, beetles and the beginning of the ends. - McGregor (BioEssays, 2006)
Recent papers investigating the genes regulating early embryogenesis in the wasp Nasonia vitripennis and the beetle Tribolium castaneum have provided us with important clues as to how early development is controlled in insects other than higher dipterans such as Drosophila melanogaster. The results of these studies demonstrate that in insects that do not have bicoid, anterior patterning is regulated by a combination of maternal orthodenticle and hunchback. Furthermore, during the evolution of long-germ-band development, Nasonia and Drosophila may have evolved different mechanisms to pattern posterior segments, marginalising the important role of the terminal system in short-germ-band embryos.